Cognitive Linguistics (De Gruyter Mouton, 1990)
Cognitive Linguistics presents a forum for linguistic research of all kinds on the interaction between language and cognition. The journal focuses on language as an instrument for organizing, processing and conveying information. It is devoted to high-quality research on topics such as the structural characteristics of natural language categorization and the functional principles of linguistic organization.